Why victimology should focus on all victims, including all missing and disappeared persons. Issue 2 (May 2019) - Sarkin, Jeremy
This article examines issues concerning the scope and role of victimology specifically as far as they relate to missing and disappeared persons. It argues that victimology ought to have a greater effect on the world by dealing with more victims, and that it should not be a solely academic discipline. It is contended that victimology should confront the real issues that arise for the victims after the crimes they suffer, and thus it needs to play a far more pragmatic, practical role. It is reasoned that broadening the study of who victims are, how they become victims and how their fate and suffering could have been avoided will also have a meaningful effect. This is also true regarding what can be done to reduce the numbers of (potential) victims. The article specifically calls on victimology to deal with victims who have gone missing. It argues that even amongst victimologists studying the widest variety of affected victims, there is almost no focus on the missing. The article goes into detail about who the missing are, and analyses the circumstances surrounding missing persons, whether as a result of war, human rights abuses such as enforced disappearances, or disasters, organized violence, migration and many more. The article also touches upon the processes of finding missing persons and considers their legal, technical and societal implications.